Ethnoecology in classrooms: a proposal for teacher training in the context of traditional communities: une proposition de formation des enseignants contextualisée aux communautés traditionnelles (2021)
In this article, we present and discuss the results of a research that aimed to analyze didactic interventions developed by teachers in initial training in biology during a university extension class focused on the teaching of intercultural ecology. The approach of the study is qualitative with an analysis of the communicative approach in the interventions carried out by teachers in initial training. Based on the data presented, it is possible to infer that teachers in initial training were not able to accurately introduce intercultural dialogue to students, which reveals an authoritative interactive-type communicative approach during their interventions. However, we realized that there was an intention to promote intercultural dialogue and the inclusion of ethno-ecological elements in their classes. This study indicates that the training of biology teachers sensitive to cultural diversity is a slow and complex process, which should not occur at specific moments during the initial training period, but rather should stimulate in university students more extensive experiences on the relationship between university and school.